KONDISI LINGKUNGAN PEMBELAJARAN BAHASA INDONESIA DALAM KELUARGA SISWA KELAS XI IPS 3 SMA N 1 PURWANEGARA BANJARNEGARA (Suatu Kajian Fenomenologi) - Prasetyo, Eko (Ruang Kata, 2022)
The purpose of this study was to find out about the form of the Indonesian language learning environment in the family for student of class XI IPS 3 SMA N 1 Purwanegara Banjarnegara. To gain an understanding of the student learning environtment in the family based on student experience, the researcher used a qualitative approach with the phenomenological method. From the result of the study, it can be explained that to create a conducive and comfortable learning environment in the family needed the availability of several learning facilities. Those are: (1) student have a room to study; (2) the room has good lighting; (3) the room has a room temperature controller; (4) have a comfortable and conducive learning atmosphere; (5) not all have study chairs and desks, but still comfortable studying on the carpet, guest chairs, on the floor or on the bed; (6) has cupboards and bookshelves; (7) have all the necessary study equipment; and (8) most of the students stated that they felt comfortable studying in a family environment. Based on these data, the researcher concluded that the support of a complete and conducive learning environment makes students able to study comfortably so that they can make learning more effective and efficient. Keywords: Learning Environment, Phenomenology